Культовые зольники скифского времени - Русанова, И.П. (Материалы по археологии, истории и этнографии Таврии, 1998)
An ashpit is an artificial mound consisting of some layers of ashes with lots of broken crockery, bones of arimals and domestic things, usually they are considered to be just "garbage piles" and no due attention is given to them. Religious character of ashpits belonging to the population of forest-steppe zone of Scythian period is defined by some peculiarities analogies with Greek ashpits, religious meaning of which is testified in ancient written sources; the structure of ashpiles pointing to repeated usage of them and periodic kindling of fire on them; a fence around them as a symbolic protection w'hich is characteristic for many sacreficial monuments; the location of ashpits on earlier cult places or near cult constructions, sacrificial composition of finds which was characteristic for majority of sanctuaries. The earliest ashpits are known in the Danube and Carpathian regions since the epoch of bronze and from there the custom of its construction could spread on the territory of the Northern Black Sea Coast among the tribes with farming-cattle breeding economy and where there was a cult of fire and hearth.